Population‐Based Study of Attitudes toward BRCA Genetic Testing among Orthodox Jewish Women. Issue 3 (30th November 2016) - Tang, Eve Y.; Trivedi, Meghna S.; Kukafka, Rita; Chung, Wendy K.; David, Raven; Respler, Leah; Leifer, Sarah; Schechter, Isaac; Crew, Katherine D.
Abstract: Given the high prevalence (1 in 40) of BRCA1 and BRCA2 mutations among Ashkenazi Jews, population‐based BRCA genetic testing in this ethnic subgroup may detect more mutation carriers. We conducted a cross‐sectional survey among Orthodox Jewish women in New York City to assess breast cancer risk, genetic testing knowledge, self‐efficacy, perceived breast cancer risk and worry, religious and cultural factors affecting medical decision‐making. We used descriptive statistics and multivariable logistic regression models to identify predictors of genetic testing intention/uptake. Among evaluable respondents ( n = 243, 53% response rate), median age was 25 and nearly half (43%) had a family history of breast cancer. Only 49% of the women had adequate genetic testing knowledge and 46% had accurate breast cancer risk perceptions. Five percent had already undergone BRCA genetic testing, 20% stated that they probably/definitely will get tested, 28% stated that they probably/definitely will not get tested, and 46% had not thought about it. High decision self‐efficacy, adequate genetic testing knowledge, higher breast cancer risk, and overestimation of risk were associated with genetic testing intention/uptake. Decision support tools that improve knowledge and self‐efficacy about genetic testing may facilitate population‐based BRCA testing among Orthodox Jews.